ASESMEN ALTERNATIF DALAM PEMBELAJARAN JARAK JAUH PADA MASA DARURAT PENYEBARAN CORONAVIRUS DISEASE (COVID-19) DI INDONESIA - Iqbal Faza Ahmad (Nurul Jadid University, 2020)
The implementation of distance education during the spread of the Covid-19 pandemic raises various problems, especially about the process of student learning assessment. Therefore there is a need for alternative assessment models that support good and effective distance learning processes, both for teachers and students. This paper seeks to provide an overview of alternative forms of assessment and evaluation, which can be used as a reference for educators in assessing and evaluating the learning outcomes of distance learners in the Corona pandemic that is sweeping Indonesia. This research is a type of library research. Researchers obtain data from the results of the study of literature from a variety of books, journals, scientific works, and also other documents that examine the assessment and evaluation of learning, both in general and specifically examine the assessment and evaluation of distance learning. The results of this study are several forms of assessment models that can be applied in the distance learning process, including online-based assessment, portfolio assessment, and self-assessment.